Resumption of injecting drug use following release from prison in Australia. - Winter, R.; Young, Jesse; Stoové, M.; Agius, P.; Hellard, M.; Kinner, S. (Elsevier Ireland Ltd, 2016)
INTRODUCTION: Ex-prisoners with a history of injecting drug use (IDU) experience disproportionate drug-related harm. Rapid resumption of substance use following prison release is common and evidenced in high rates of overdose mortality. However, few studies have documented the rate of IDU resumption following prison release or identified risk factors for relapse. METHODS: Structured interviews were conducted with 533 adults with a history of IDU in Queensland, Australia prior to release from prison and approximately 1, 3 and 6 months post-release. Incidence of self-reported IDU resumption was calculated overall and for each follow-up interval. Risk factors associated with time to resumption of IDU were estimated using discrete-time survival analysis. RESULTS: IDU resumption was reported by 41% of participants during a median of 98days of follow-up (IQR=94-121), an overall crude incidence of 1.06 per person-year. The highest rate was observed in the first month (23%; crude incidence 2.24 per person-year). In adjusted discrete-time survival analyses, being unemployed at the previous interview (AHR=1.59; 95%CI:1.10-2.30), shorter incarceration (=90days vs. >365days; AHR=2.20; 95%CI:1.33-3.65), and IDU during the index incarceration (AHR=2.80; 95%CI:1.92-4.09) were significantly associated with time to IDU resumption; parole was protective (AHR=0.66; 95%CI:0.47-0.92). CONCLUSIONS: Evidence-based efforts to prevent IDU in prison and IDU resumption after release are important for both prisoner and public health. Enhancing opportunities for employment and capitalising on the short-term benefits of parole for ex-prisoners may delay resumption of IDU after release from prison. These strategies should complement rather than replace harm reduction efforts for this high-risk population.